2022
DOI: 10.1021/jacsau.2c00273
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Design and Thermal-Induced Organization of Interfacial Water Structure to Regulate the Wetting State of Surfaces

Abstract: Smart surfaces with superhydrophobic/superhydrophilic characteristics can be controlled by external stimuli, such as temperature. These transitions are attributed to the molecular-level conformation of the grafted polymer chains due to the varied interactions at the interface. Here, tunable surfaces were prepared by grafting two well-known thermo-responsive polymers, poly( N -isopropylacrylamide) (PNIPAM) and poly(oligoethylene glycol)methyl ether acrylate (POEGMA 188 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…At 20°C, the higher ratio suggested that the PN10-g-SEC surface had a larger amount of bound water, with the hydrophilic C=O and -NH 2 groups predominantly positioned at the air/PN-g-SEC/water interface. Conversely, the spectrum displayed a signi cant reduction in the 4-HBW/BW ratio at 40°C, indicating that the water underwent a transformation into a less ordered and weaker hydrogen-bonded structure, while the hydrophobic -CH 3 groups rearranged and exposed at the interface 7 (Figure 2e). Taking advantage of this characteristic together with the hierarchical structure on the outer surface of SEC, we obtained the thermo-responsive surfaces with switchable wettability transition as illustrated in our previous study 7 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At 20°C, the higher ratio suggested that the PN10-g-SEC surface had a larger amount of bound water, with the hydrophilic C=O and -NH 2 groups predominantly positioned at the air/PN-g-SEC/water interface. Conversely, the spectrum displayed a signi cant reduction in the 4-HBW/BW ratio at 40°C, indicating that the water underwent a transformation into a less ordered and weaker hydrogen-bonded structure, while the hydrophobic -CH 3 groups rearranged and exposed at the interface 7 (Figure 2e). Taking advantage of this characteristic together with the hierarchical structure on the outer surface of SEC, we obtained the thermo-responsive surfaces with switchable wettability transition as illustrated in our previous study 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the spectrum displayed a signi cant reduction in the 4-HBW/BW ratio at 40°C, indicating that the water underwent a transformation into a less ordered and weaker hydrogen-bonded structure, while the hydrophobic -CH 3 groups rearranged and exposed at the interface 7 (Figure 2e). Taking advantage of this characteristic together with the hierarchical structure on the outer surface of SEC, we obtained the thermo-responsive surfaces with switchable wettability transition as illustrated in our previous study 7 . By adjusting the polymer grafting density, we successfully obtained pollen microparticles with hydrophilic/hydrophobic transition states on the PN20-g-SEC surfaces (Figure S5) and the constructed PN10-g-SEC surfaces exhibited remarkable superhydrophobic/ superhydrophilic wettability transition characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, some recent studies on the interfacial water structure indicated that the intrinsic wetting threshold for hydrophilic/hydrophobic was close to ∼65° rather than 90° [25] . This was associated with the water molecules forming denser structures at the solid/liquid interface, such as trihedral or tetrahedral conformation on hydrophilic surface, while the water molecules display weak interactions with hydrophobic surface, assembling into looser or non‐hydrogen‐bond water structures [26] …”
Section: Superhydrophobicity: Definitionmentioning
confidence: 98%
“…[25] This was associated with the water molecules forming denser structures at the solid/liquid interface, such as trihedral or tetrahedral conformation on hydrophilic surface, while the water molecules display weak interactions with hydrophobic surface, assembling into looser or non-hydrogen-bond water structures. [26] Young's equation quantitatively represents the relationship between CA, liquid surface tension γ Lv , and interfacial tension γ sL and solid surface tension γ sv for an ideal flat surface with homogeneous physical/chemical properties as described by Equation (1):…”
Section: Flat Surface and Young's Equationmentioning
confidence: 99%